Jakie są granice x jeśli (2x-1) / (x + 5)> = (x + 2) / (x + 3)?

Jakie są granice x jeśli (2x-1) / (x + 5)> = (x + 2) / (x + 3)?
Anonim

Odpowiedź:

x = -5, x = -3, x = 1-sqrt (14), x = 1 + sqrt (14) x=5,x=3,x=114,x=1+14

> = "występuje dla" x <-5 "i" x> = 1 + sqrt (14) "i"

-3 <x <= 1-sqrt (14) „.”

Wyjaśnienie:

=> (2x-1) / (x + 5) - (x + 2) / (x + 3)> = 0

=> ((2x-1) (x + 3) - (x + 2) (x + 5)) / ((x + 5) (x + 3))> = 0

=> (2x ^ 2 + 5x-3-x ^ 2-7x-10) / ((x + 5) (x + 3))> = 0

=> (x ^ 2 -2x-13) / ((x + 5) (x + 3))> = 0

=> ((x - 1 - sqrt (14)) (x - 1 + sqrt (14))) / ((x + 5) (x + 3))> = 0

"Mamy następujące zera w rzędzie wielkości:"

…. -5 …. -3 …. 1-sqrt (14) …. 1 + sqrt (14) …..

-----------0+++

-------0+++++++

-----0+++++++++

--0++++++++++++

'========================='

++0---0++0---0+++

„Widzimy„> = 0 ”występuje dla„ x <-5 ”i„ x> = 1 + sqrt (14) ”i„

-3 <x <= 1-sqrt (14) „.”